PARTISIPASI MASYARAKAT DALAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KABUPATEN KEBUMEN - Widodo (Universitas Slamet Riyadi, 2022)
Complete Systematic Land Registration (CLSR) is a national program of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency to accelerate land registration throughout Indonesia. The CLSR target in 2017 was 5 million certificates, 7 million certificates in 2018, 9 million certificates in 2019 and for 2020-2025 the target is 10-13 million certificates every year. The purpose of this study was to analyze differences in community participation in the CLSR program carried out by the Land Office of Kebumen Regency (Case Study in Krakal Village, Alian District and Pecarikan Village, Prembun District). This research uses a case study approach with qualitative methods. Data collection was carried out by observation, interviews, questionnaires and documentation. The analysis of community participation in this study used the participation theory proposed by Sherry R. Arnstein (1969), which divides the level of community participation into 8 levels, namely: citizen control, delegated power, partnership, placation, consultation, informing, therapy and manipulation. The conclusion obtained in this study is that there are differences in the level of community participation in the implementation of CLSR in Krakal Village and Pecarikan Village. The participation level of the residents of Krakal Village in the implementation of CLSR is higher than that of Pecarikan Village residents. Factors that affect the level of participation are differences in responses at each stage of CSLR implementation, differences in people's awareness to certify their land, coordination and communication between relevant stakeholders, obstacles in mobilizing community participation in the CSLR program. Recommendations in increasing community participation are increasing understanding of the importance of land certificates, solving solutions to negative public perceptions about land certificates, increasing communication and coordination between stakeholders and expanding public space as a channel for community participation. Keywords: community participation, CLSR, Kebumen Regency Land Office.